Periungual lesions secondary to chemotherapy with docetaxel - Dawid Sigorski; Agnieszka Markiewicz; Agnieszka B. Owczarczyk-Saczonek; Paweł Różanowski; Anna Kułakowska; Waldemar J. Placek; Aneta Lebiedzińska (Termedia Publishing House, 2020)
Chemotherapy is a basic treatment method of neoplasms at a systemic stage. Chemotherapy regimens including docetaxel are commonly used in every day clinical practice. Docetaxel is a chemotherapeutic agent that causes skin toxicity among other side effects. It involves alopecia and periungual lesions. The latter may cause pain as well as discomfort, and constitute a cosmetic problem. Sometimes they may lead to termination of the therapy due to negative effects on the quality of life and everyday activities. The aim of the article is to present clinical problems of patients undergoing chemotherapy with docetaxel that experience periungual lesions, and show treatment methods from a dermatologist's perspective. Moreover, prophylactic methods that prevent appearance of severe lesions are presented.